Mr. Kaldor's Theory of Income Distribution - Atsumi, Hiroshi (Review of Economic Studies, 1960)
Journal Article Mr. Kaldor's Theory of Income Distribution Get access Hiroshi Atsumi Hiroshi Atsumi Osaka Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 2, February 1960, Pages 109–118, https://doi.org/10.2307/2296131 Published: 01 February 1960